La philosophie dans le boudoir - Sade Marquis de 1740-1814 (Paris Bookking International, 1994)
'La philosophie dans le boudoir' is a 1795 book by the Marquis de Sade written in the form of a dramatic dialogue. Though initially considered a work of pornography, the book has come to be considered a socio-political drama. Set in a bedroom, the two lead characters make the argument that the only moral system that reinforces the recent political revolution is libertinism, and that if the people of France fail to adopt the libertine philosophy, France will be destined to return to a monarchic state. In the chapter titled "Fifth Dialogue", there is a lengthy section where the character Chevalier reads a philosophical pamphlet titled "Frenchmen, Some More Effort If You Wish To Become Republicans". The pamphlet clearly represents Sade's philosophy on religion and morality, a philosophy he passionately hopes the citizens of France will embrace and codify into the laws of their new republican government.
Donatien Alphonse François, Marquis de Sade (1740-1814), was a French nobleman, revolutionary politician, philosopher and writer famous for his literary depictions of a libertine sexuality. His works include novels, short stories, plays, dialogues, and political tracts. In his lifetime some of these were published under his own name while others, which Sade denied having written, appeared anonymously.
Keywords: 18th Century (1701-1800); 20th Century (1901-2000); Philosophy; Crescendo; Ethics; France